Gains and losses on the road to understanding Alzheimer’s disease (Swiss Medical Weekly, 2015)
Alzheimer’s disease (AD) is a neurodegenerative disorder and the most common cause for dementia, which affects approximately 120 thousand people in Switzerland and 35 million worldwide. Aging is a major risk factor for developing AD and thus, as our societies are growing older, we face great challenges to find treatment strategies. The disease is characterised by loss of memory, deposition of extracellular amyloid plaques containing Aβ peptides and intraneuronal tangles of the tau protein. To date, there is no effective treatment and the cause of the disease is still debated. The Schweizerische Alzheimervereinigung states that we need “continuous manifold research” into all possible causes of AD to find a cure for this disease. Fitting this proposition, a recent publication by Xia et al. (2015) described a novel mouse model that for the first time reproduces cortical neuron death as observed in human AD cases. At the same time, this publication questions the major theory of AD pathogenesis and points towards different treatment avenues that should be followed to find a cure for AD. Key words: Alzheimer’s disease; amyloid precursor protein (APP); nuclear signaling; presenilin; AICD; neurodegeneration